Morfoanalitica therapy in quality of life, stress and flexibility of women after breast cancer surgery. - Pachioni, Fernanda Stellutti Magrini; Fregonesi, Cristina Elena Prado Teles; Mantovani, Alessandra Madia (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Breast cancer is a disease with multifactorial causes. From diagnosis to surgical treatment, women with breast cancer experienced severe physical and emotional repercussions that may have an impact on their quality of life, stress and flexibility. Objective: The present study aimed to verify the effect of Morfoanalitica Therapy (TM) on quality of life, stress and flexibility after breast cancer surgery in women. Method: The study included 10 postoperative women for breast cancer with evaluation of personal and anthropometric data. Then they were invited to answer the questionnaires of the quality of life - SF -36 and the inventory of symptoms of stress (ISS) Lipp. In addition, the functional test for the evaluation of flexibility called bank Wells test and side inclination of the torso were carried out. The questionnaires and functional tests were performed before and after the intervention period, with 16 individual sessions of TM, once a week, during 60 minutes. Results: Significant changes after treatment with TM fields, physical (p = 0.0301) and general health (p = 0.0378) of the SF -36 were found. The stress had a significant improvement in phase 1 (p = 0.0424) and phase 3 (p = 0.0348). There were also significant improvements in flexibility at the bank Wells test (p = 0.0024) and ipsilateral lateral (p = 0.0130) and contralateral (p = 0.0039) surgery. Conclusion: The intervention with the TM domains showed significant effects on physical aspects and general health quality of life, stress and flexibility of women after breast cancer surgery.